Impacts of Spatial, Environmental, and Compositional Differences on Community-level Flowering Phenology - (:unkn) unknown (My University, 2014)
This dissertation investigates three important topics related to flowering phenology throughout the United States. First, this work evaluates the utility of herbarium records for estimating historical variation in community-level flowering phenology, and evaluate the relationship of such estimates to satellite-derived greenup timing at regional scales. This dissertation then reconstructs historical variations in flowering phenology throughout the spring, summer, and autumn across South Carolina for the years 1951 through 2009. These estimates will then be compared to seasonal temperature variations throughout this period. Finally, this dissertation develops novel herbarium-based methods to separate intraspecific phenological variations over space from changes in flowering time derived from differences in community composition, and evaluate the contributions of compositional differences to spatial variation in community-level flowering times throughout the early, mid, and late portions of the growing season and across a variety of temperate environments within the continental United States. The results of these inquiries demonstrate that phenological information included in digital herbarium archives can produce annual phenological estimates correlated to satellite-derived green wave phenology. Examinations of historical flowering throughout South Carolina also determined that species that flower near the onset of the growing season advanced under increasing mean March temperatures, while late spring through mid-summer flowering exhibited delays in response to higher February temperatures. Thus, although no long-term phenological trends were detected, these findings indicate that flowering synchrony may undergo significant restructuring in response to warming spring temperatures, even in humid subtropical environments. Examinations of composition-derived phenological variation over space determined that, although typically smaller than intraspecific variations, composition-derived shifts in flowering time explained up to 49.3% of overall phenological variation, and were the most responsive to differing climate conditions within xeric regions and among late-flowering species. These results demonstrate that interspecific differences in flowering time play a significant role in determining the composition of the plant community over space. Additionally, these findings indicate that impacts of flowering phenology on community assemblage are most severe within xeric regions and throughout the late-flowering portion of the plant community
Keywords: Climate; Climate Change; Herbarium; Phenology